Metallo-Phthalocyanines Based Photocapacitors - Tataroglu, A.; Koran, Kenan; Caliskan, Eray; Al-Sehemi, Abdullah G.; Gorgulu, Ahmet Orhan; Al-Ghamdi, Ahmed; Yakuphanoğlu, Fahrettin (Springer, 2019)
The novel metallo-phthalocyanines (4-6) were obtained from the reactions of gereniol substituted phthalonitrile compound (3) with corresponding metal salts (Co (II), Cu (II) and Zn (II) acetates). The electrical and photoconductive properties of Al/p-Si/organic complex/Al devices with cobalt (4), copper (5) and zinc (6) phthalocyanines complexes containing geraniol as side groups were studied by using optoelectrical measurements at various sunlight intensites. The transient photocurrent and photocapacitance were measured as a function of time. Experimental results indicate that the prepared diodes exhibit both photodiode and photocapacitive behavior. Consequently, it is evaluated that the studied devices can be used as a photocapacitor in optical applications.
Keywords: Diode; Metallo-phthalocyanines; Transition metals complexes; I-V characteristics; Transient photocurrent; Photocapacitance